Performance of Bemisia tabaci Biotype B on Soybean Genotypes - Cruz, P. L. [UNESP]; Baldin, E. L.L. [UNESP] (Springer Nature, 2017)
Bemisia tabaci (Genn.) (Hemiptera: Aleyrodidae) has been recognized as an important pest of many agricultural systems including soybean [Glycine max (L.) Merrill] crops. As an alternative to chemical control, the use of resistant genotypes represents an important tool for integrated pest management (IPM). This study aimed to evaluate the biological development of Bemisia tabaci biotype B confined on 13 soybean genotypes under greenhouse conditions. Initially, the nymphal period, complete development period (egg–adult), and the viability of the silverleaf whitefly nymphs were evaluated in all genotypes. Then, four genotypes promising for resistance (‘Jackson,’ UX-2569-159, ‘P98Y11,’ and ‘TMG132 RR’) and a susceptible genotype (PI-227687) were selected for further assays, where two insect populations were compared: a first population from the initial rearing (cabbage plants) and another corresponding to insects previously reared out on the selected genotypes. In addition to the parameters evaluated in preliminary tests, we also determined the viability and incubation period of eggs. Moderate levels of resistance (antibiosis/antixenosis) to B. tabaci biotype B were found in three genotypes. ‘P98Y11’ and ‘TMG132 RR’ were less suitable for insect development, extending the development cycle, and UX-2569-159 caused high nymphal mortality. We did not observe a significant increase in the level of plant resistance by the use of previously stressed insects. This suggests that the evaluation of a single whitefly generation may be sufficient to make correct decisions on promising soybean genotypes.
Keywords: Antibiosis; Antixenosis; Glycine max; Host plant resistance; Silverleaf whitefly